Length-Weight Relationship and Sex Ratio Blood Clam (Anadara granosa) in Rangsang Barat Waters Kepulauan Meranti District, Riau Province - Efriyeldi Efriyeldi; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Anadara granosa is one of the bivalves that are often found in public markets. This study aimed to study the relationship between length-weight and sex ratio of blood clams (A. granosa) in the coastal waters of West Rangsang. Sampling was carried out every month at three stations. Shells were collected from a 1 x 1 m2 plot on a quadratic transect. The relationship between length and weight was analyzed by regression analysis. The sex ratio between the number of female and male blood clams in each month of sampling was calculated and followed by the Chi square test to test the similarity. The results showed that the relationship between length and weight of A. granosa was positive allometric. The sex ratio of female and male blood clams in the waters of West Rangsang is not balanced. The number of male blood clams is more than the female